Lethal Pneumonia Cases in Mojiang Miners (2012) and the Mineshaft Could Provide Important Clues to the Origin of SARS-CoV-2 - Rahalkar, Monali C.; Bahulikar, Rahul A. (Frontiers in Public Health, 2020)
With the COVID-19 pandemic reaching its worse heights, everyone is genuinely interested in the origin of SARS-CoV-2. In our quest, we started with two important questions: First, were there any similar atypical pneumonia outbreaks, even on a smaller level, reported in between SARS (2004) and COVID-19 (2019) from China? Secondly, where did the beta-coronavirus most closely related to date with SARS-CoV-2 at the genome sequence level, strain RaTG13 (CoV4991) sampled from a horseshoe bat in Yunnan province, exactly come from? It was found that RaTG13/CoV4991 was collected from Tongguan mineshaft in Mojiang, Yunnan, China, in 2013. Surprisingly, the same mineshaft was also associated with a severe pneumonia-like illness in miners in 2012 killing three of the six miners. A Master’s thesis (in the Chinese language) was found on the cnki.net website which described in detail the severe illness in miners. The thesis concluded that a SARS-like CoV originating from Chinese horseshoe bats (Rhinolophus) was the predicted causative agent. The cases were remotely monitored by a prominent pulmonologist in China. The retrospective analysis of the pneumonia cases shows striking similarities with COVID-19. Bilateral pneumonia, vascular complications like pulmonary thromboembolism, and secondary infections are the main similarities. The treatment regimes were similar to the currently given treatment for COVID-19. We propose that the Mojiang mineshaft and the miners' illness cases could provide important clues to the investigation of the origin of SARS-CoV-2. The cases should be studied by various academicians, researchers, and medical professionals. Many important questions are raised in this context.